THE SOCIOGRAPH: FRIENDSHIP-BASED GROUP LEARNING IN THE MATHEMATICS CLASS - Sri Adi Widodo; Turmudi Turmudi; Jarnawi Afgani Dahlan; Somchai Watcharapunyawong; Hasti Robiasih; Mustadin Mustadin (IKIP Siliwangi and I-MES, 2023)
Mathematics class can cause many problems if students do not organize diversity and habits correctly. Using a sociograph to form a mathematics study group is one way to organize assortment in the mathematics class. Sociograph is a friendship pathway that appears in a math class. In this sense, this study aims to determine the impact of forming study groups based on friendship in a mathematics class on problem-solving abilities. A quasi-experimental research design with 30 students was used. A friendship questionnaire and a problem-solving test were used as instruments. In addition, an independent t-test was used to analyze the data. The study results indicate that study groups formed through friendship pathways (sociograph) have a more significant effect than those formed through other means. As a result, the formation of heterogeneous groups based on friendship can be used as an alternative to the formation of study groups.